A Pilot Experiment in Responding to Individual Patient Requests for Compassionate Use of an Unapproved Drug: The Compassionate Use Advisory Committee (CompAC). (March 2019) - Caplan, Arthur; Bateman-House, Alison; Waldstreicher, Joanne; Fedor, Lisa; Sonty, Ramana; Roccia, Tito; Ukropec, Jon; Jansson, Rick
Background: Janssen Research & Development, LLC, part of the Janssen pharmaceutical companies of Johnson & Johnson, and NYU School of Medicine partnered to establish the Compassionate Use Advisory Committee (CompAC) to evaluate the use of an independent, external, expert committee in ensuring transparent, fair, beneficent, evidence-based, and patient-focused compassionate access to investigational medicines, a public health challenge that has been an ongoing issue for over 3 decades. Methods: To this end, NYU School of Medicine was responsible for the formation, member selection, and operation of CompAC, consisting of physicians, ethicists, and patient advocates, under Johnson & Johnson's sponsorship. Results: A pilot was successfully run using CompAC to provide recommendations on compassionate use access to a Johnson & Johnson oncology investigational asset called daratumumab. Conclusion: This innovative model provides a framework that can be emulated by the industry globally.